Focused Ion Beam in the Study of Biomaterials and Biological Matter - Kathryn Grandfield; Håkan Engqvist (Advances in Materials Science and Engineering)
The application of focused ion beam (FIB) techniques in the life sciences has progressed by leaps and bounds over the past decade. A once dedicated ion beam instrument, the focused ion beam today is generally coupled with a plethora of complementary tools such as dual-beam scanning electron microscopy (SEM), environmental SEM, energy dispersive X-ray spectroscopy (EDX), or cryogenic possibilities. All of these additions have contributed to the advancement of focused ion beam use in the study of biomaterials and biological matter. Biomaterials, cells, and their interfaces can be routinely imaged, analyzed, or prepared for techniques such as transmission electron microscopy (TEM) with this comprehensive tool. Herein, we review the uses, advances, and challenges associated with the application of FIB techniques to the life sciences, with particular emphasis on TEM preparation of biomaterials, biological matter, and their interfaces using FIB.